Development of a cryogenic indentation tool with in situ optical observation, application to the mechanical characterization of II–VI semiconductors. (18th February 2021) - Broult, T; Kerlain, A; Destefanis, V; Guinedor, P; Bourhis, E Le; Patriarche, G
Abstract: Infrared detectors based on II–VI semiconductors are cooled from room temperature (RT) to cryogenic temperatures between 80 K and 150 K in order to operate with strong requirements regarding sensor performances for infrared detection. At these cryogenic temperatures, the mechanical properties of II–VI alloys have to be known in detail to improve handling, use and lifetime of infrared sensors. We have developed a cryogenic indentation tool and in situ measured the mechanical properties of CdZnTe alloys at both RT and 90 K. CdZnTe hardness increases by a factor of about 3 when cooling from RT to 90 K, from 0.6 GPa to 1.6 GPa. The plastic flow driving mechanism shows at least two different domains with activation energies around 0.01 eV at low temperatures and around 0.05 eV at RT, showing an increase by a factor of about 5. These two domains might be 'connected' by an intermediate domain in the 235 K–290 K temperature range. Radial cracks can be in situ detected. Toughness of CdZnTe alloys also increases dramatically by a factor of about 2 with cooling down to cryogenic temperature from 0.13 MPa.m 1/2 at RT to 0.25 MPa.m 1/2 at 90 K.